2012
DOI: 10.1016/j.infbeh.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal play behaviors, child negativity, and preterm or low birthweight toddlers’ visual–spatial outcomes: Testing a differential susceptibility hypothesis

Abstract: Objective We examined the joint roles of child negative emotionality and parenting in the visual-spatial development of toddlers born preterm or with low birthweights (PTLBW). Method Neonatal risk data were collected at hospital discharge, observer- and parent-rated child negative emotionality was assessed at 9-months postterm, and mother-initiated task changes and flexibility during play were observed during a dyadic play interaction at 16-months postterm. Abbreviated IQ scores, and verbal/nonverbal and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…For the purposes of this review, responsivity was more narrowly characterized as parental sensitivity, such that a parent responds to a child's signalling (Johnson et al, 2009;Treyvaud et al, 2009;Treyvaud et al, 2016). This concept is well described in attachment theory (Dilworth-Bart et al, 2012) and may explain why parental responsivity is strongly associated with improved child cognitive and behavioural outcomes in former preterm infants. These outcomes include improved scores on standard assessments such as the Bayley and Stanford-Binet tests, increased math, language, and reading skills, and decreased emotional symptoms, conduct problems, hyperactivity, and/or peer difficulties (Feldman et al, 2002;Smith et al, 2001;Treyvaud et al, 2016).…”
Section: Associations Between Parental Warmth or Rejection Andmentioning
confidence: 99%
See 3 more Smart Citations
“…For the purposes of this review, responsivity was more narrowly characterized as parental sensitivity, such that a parent responds to a child's signalling (Johnson et al, 2009;Treyvaud et al, 2009;Treyvaud et al, 2016). This concept is well described in attachment theory (Dilworth-Bart et al, 2012) and may explain why parental responsivity is strongly associated with improved child cognitive and behavioural outcomes in former preterm infants. These outcomes include improved scores on standard assessments such as the Bayley and Stanford-Binet tests, increased math, language, and reading skills, and decreased emotional symptoms, conduct problems, hyperactivity, and/or peer difficulties (Feldman et al, 2002;Smith et al, 2001;Treyvaud et al, 2016).…”
Section: Associations Between Parental Warmth or Rejection Andmentioning
confidence: 99%
“…Parental coercion is coded during parent-child tasks using various instruments that determine parental intrusiveness, restrictiveness, taking over for the child too quickly, over controlling, or directive behaviours (Dilworth-Bart et al, 2012;Foster-Cohen, Friesen, Champion, & Woodward, 2010;Hebert, 2002;Poehlmann et al, 2011;Poehlmann et al, 2012;Shah et al, 2013;Smith et al, 1996;Smith et al, 2000;Treyvaud et al, 2009;Treyvaud et al, 2016). Aggregate data support no positive or negative associations between parental coercion and subsequent child outcomes in former preterm infants.…”
Section: Associations Between Parental Warmth or Rejection Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was not designed to examine whether differences between children in high poverty vs. affluent communities in academic outcomes were mediated by differences in EF. In a more direct assessment of mediation in a study of 49 children (54 -66 months old) in a small town, Dilworth-Bart et al (2012) found that EF did significantly mediate the effects of socioeconomic status (SES) on math competency, but notes that the study was limited both by sample size and constricted range of SES, as the children were mostly from well-educated middle-income homes. The most compelling existing data of mediation by EF deficits of the effects of poverty on academic outcomes is provided by a study of the development of brain regions important in EF (Hair et al 2015).…”
Section: Introductionmentioning
confidence: 99%